Analysis of the complications of volar plate fixation for the treatment of distal radius fractures Frykman type 3 - 6 - Xaso, Sibulele (My University, 2021)
The aim of our study was to analyse complications after open reduction and internal fixation (ORIF) using a volar plate in distal radius fractures. Our study’s hypothesis was that “complications” rates after ORIF using a volar plate were lower at Chris Hani Baragwanath Academic Hospital (CHBAH) than those reported in the current literature. We conducted a retrospective study with prospective recall, with a sample-size of 62 patients. The selected patients were those who were managed operatively between 01 July 2015 and 31 June 2017. Moreover, these participants were 18 years of age and older, active male and female patients and had Frykman types 3 ‒ 6 distal radius fractures. Data collection was done during the orthopaedic trauma upper limb and hands clinics. Data analysis was done using STATA software package, version 14 and frequency Tables were used. Our results showed variable complication rates in comparison to those reported in the literature. In terms of the relationship between the complications versus (i) surgical and (ii) patient-related factors, it was noted that senior surgeons had the least complications and better functional scores than their junior counterparts. We also found that, patients with increased number of complications had poor hand functional scores. Finally, our study’s hypothesis was disproved after we got a higher incidence of complications than that reported in available literature
A researcher report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine, 2021